The Role of Traditional and New Media in Stirring up Sport Prejudiced-Attitudes among Youth from University Students' Point of View in Riyadh - Abdulaziz Mohammed A. Bin-Hussein (University of Science and Technology, Yemen, 2018)
This study aimed to explore perceptions of university students regarding the role of traditional and new media in stirring up prejudiced attitudes and sport violence among youth population in the city of Riyadh. The study included a discussion of the theoretical frameworks of prejudiced attitudes relating to sport contexts. Related past studies were also reviewed. The study utilized a descriptive approach (survey and comparative study). In this study, the research population represented all university students in Riyadh; and a sample of 462 students served as the participants for the study. A questionnaire was designed as a tool for collecting the study data. Statistical analyses of the participants' responses revealed an impact of the media (traditional and modern) in the development and spread of sport prejudice and sport violence among the youth community. These results were consistent with that of other researchers, in respect to the essential role of the media in shaping the beliefs and concepts of the masses. On the other hand, the results of the study showed that different mass media, have different level of impact in building up sport prejudiced attitudes among youth. The results of the study also revealed the superiority of modern means of communication to traditional media in terms of the impact on the public, with regards to the ability to stimulate the feelings and thoughts of sport intolerance and violence among sport fans. In light of the results of the study, a number of ways and measures to combat apparent sport intolerance and sport violence were recommended. Some suggestions for future research were also provided. Keywords: Traditional media, New media, Sport prejudiced-attitudes, Saudi youth.